THE INFLUENCE OF BRAND IMAGE, PRODUCT QUALITY, AND SERVICE QUALITY TOWARDS THE PURCHASE DECISION OF H&M’S CUSTOMERS IN MEDAN - Tamara Fransiska; Alfonsius Alfonsius (Jurnal Ekonomi, 2022)
&M plays a major role in the fashion industry, and it is important for brands to maintain and develop their customers' purchasing decisions. This study was conducted to measure the effect of brand image, product quality, service quality on purchasing decisions of H&M customers in Medan. This study used a questionnaire given to H&M customers in Medan, who had visited and made purchases in the last two years before the questionnaires were distributed. The sampling method used is non-probability, namely snowball sampling. The data analysis technique used is multiple linear regression. The results of H&M Medan’s customers showed that brand image had a significant partially influence on the purchase decision and product quality had a significant partially influence on the purchase decision. Meanwhile, service quality has no significant influence on the purchase decision. Next, brand image, product quality and service quality simultaneously have a significant influence on purchase decision at H&M Medan.